PEMANFAATAN HIDROLISAT PATI SAGU SEBAGAI SUMBER KARBON UNTUK MEMPRODUKSI BIOPLASTIK POLIHIDROKSI ALKANOAT (PHA) OLEH Ralstonia eutropha PADA SISTIM KULTIVASI FED BATCH - Syamsu, K; Fauzi, A.M; hartoto, L; suryani, a; atifah, n (Badan Pengkajian dan Penerapan Teknologi, 2007)
The objective of this resarch has been to examine the utilization of hydrolysed sago starch as main substrate to produce PHA by Ralstonia eutropha using fed batch cultivation method. The results show that the hydrolysed sago starch can be used as carbon source for the production of PHA by Ralstonia eutropha. A higherformation and accumulation of PHA can be achieved through feeding of hydrolysed sago starch in a fedbatch cultivation method. The best treatment can increase the specific product yield up to 76.54% and product concentration up to 3.72 g/L.